Investigasi Awal Penggunaan Layanan Digital Perguruan Tinggi. Studi Kasus: IPB Mobile for Students - Dean Apriana Ramadhan; Firman Ardiansyah; Julio Adisantoso; Auzi Asfarian; Yani Nurhadryani (Jurnal Ilmu Komputer dan Agri-Informatika, 2022)
Digital services at universities have become necessary, especially after the Covid-19 pandemic disrupted universities. The transformation of the teaching and learning process and its supporting activities from face-to-face to online requires a support system that is inclusive and accessible to the entire higher education community. In 2020, Bogor Agricultural University launched the IPB Mobile for Students application which provides services for students digitally. This research was conducted to conduct an initial investigation of the use of the application. The investigation was carried out using a survey of 198 student respondents from the Bogor Agricultural University in February - March 2022. The questionnaire consisted of two parts: context questions to explore the use of IPB Mobile for Students by students and open questions to seek feedback from students. In general, the results of this initial investigation have insights regarding the use of digital services at IPB, especially in the IPB Mobile for Students application. It can be seen that digital services play an essential role in the teaching and learning process. Student engagement with digital services Reflects a changing pattern or transformation of the standard process for academic services in higher education. This study recommends further studies to examine the use of higher education digital services.